Long-Run Impacts of Childhood Access to the Safety Net - Hoynes, Hilary; Schanzenbach, Diane Whitmore; Almond, Douglas (American Economic Review, 2016)
We examine the impact of a positive and policy-driven change in economic resources available in utero and during childhood. We focus on the introduction of the Food Stamp Program, which was rolled out across counties between 1961 and 1975. We use the Panel Study of Income Dynamics to assemble unique data linking family background and county of residence in early childhood to adult health and economic outcomes. Our findings indicate access to food stamps in childhood leads to a significant reduction in the incidence of metabolic syndrome and, for women, an increase in economic self-sufficiency. (JEL I12, I38, J24)